A STUDY OF THE IMPORTANCE OF AGRICULTURAL LAND IN MUGHAL INDIA - Singh, Ritesh Kumar; Parveen, Shagufta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Looking at the geographical map of Mughal India, it is clear that somewhere there was jungle, somewhere there were rocky plateaus and somewhere there was desert. In West Bengal, farming was done till Sundarbans, while from Chittagong to Sylhet there were dense forests. Large scale farming was done in Bihar and Awadh. In this region too, the area from Gorakhpur to Azamgarh was covered with forests. In Agra province, farming was done on the sari land. The land of Malwa was very fertile. The forests of Berar were cut down and the land there was made cultivable. Thus it can be said that in the Mughal Empire, farming was done on all the cultivable land and the land of that time was very fertile compared to today. Usually two types of crops were sown on the land, Rabi and Kharif, but in some areas there is mention of three crops. On the basis of experience, the farmers of India had complete knowledge of farming by changing crops and they used to get more benefit from it. Special attention was given to agricultural production during the Mughal period. They considered it necessary to make the villages prosperous for the trends of the cities. They encouraged the farmers to produce more. It was the specialty of the Mughal period that more production in the agricultural sector was made the basis of industrial prosperity. Before the Mughals, among the Delhi Sultans, Balban, Ghiyasuddin Tughlaq and Muhammad Tughlaq also tried to do this, but they did not get much success in it.